Financial behavior of the millenial generation: financial literacy, financial intelligence, financial inclusion - Harun Alrasyid; Sultan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The millennial generation has become a hot discussion issue in society and is currently the main focus, because it shows substantial influence in the era of globalization. In financial management, the millennial generation faces very difficult challenges caused by lifestyle and a lack of in-depth understanding of financial aspects. This research aims to determine the influence of financial literacy, financial intelligence and financial inclusion on the financial behavior of the millennial generation. This research is quantitative research using primary data. The population in this study is the millennial generation of Palopo city aged 24 to 39 years. Those who filled out the research questionnaire were used as a sample of 70 people. The data collection technique uses a questionnaire distributed online from October to December 2023. The data collection method uses a saturated sampling method. The analysis method used is multiple linear analysis with the help of SPSS version 26 software. The research results show that partially using the t test it is concluded that financial literacy, financial intelligence and financial inclusion have a positive and significant effect on financial behavior. Simultaneously there is an influence of financial literacy, financial intelligence and financial inclusion on the financial behavior of the millennial generation in Palopo City.